2006
DOI: 10.1007/s10067-006-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in a patient with adult-onset stills disease

Abstract: Pulmonary manifestations of adult-onset Still's disease (AOSD) include aseptic pneumonitis, pleural effusions, rarely acute respiratory distress syndrome, and restrictive lung disease. Pulmonary arterial hypertension (PAH) occurs with several rheumatologic diseases, however, has only been reported once in AOSD. We describe a 29-year-old woman with a 9-year history of AOSD, who developed PAH without any other obvious cause. Therefore, we conclude that this is likely a result of pulmonary vascular changes relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Although isolated case reports of PAH, AP, and ILD in systemic JIA and adult-onset Still's disease have been pub-lished (22)(23)(24)(25)(26)(27)29,30), the findings in this study indicate that these complications may occur more commonly than previously suspected and are fatal in the majority of patients. PAH, ILD, and AP are all processes in which inflammation likely has an important role; for example, pathologic PAH specimens show an increased inflammatory perivascular infiltrate, including macrophages, dendritic cells, lymphocytes, and mast cells (31)(32)(33).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although isolated case reports of PAH, AP, and ILD in systemic JIA and adult-onset Still's disease have been pub-lished (22)(23)(24)(25)(26)(27)29,30), the findings in this study indicate that these complications may occur more commonly than previously suspected and are fatal in the majority of patients. PAH, ILD, and AP are all processes in which inflammation likely has an important role; for example, pathologic PAH specimens show an increased inflammatory perivascular infiltrate, including macrophages, dendritic cells, lymphocytes, and mast cells (31)(32)(33).…”
Section: Discussionmentioning
confidence: 50%
“…Although pleuritis, along with pericarditis, is a commonly recognized feature of systemic JIA (11,21), other pulmonary complications, such as PAH, interstitial lung disease (ILD), and alveolar proteinosis (AP) or lipoid pneumonia, are extremely rare. Prior to 2008, only scattered single case reports of PAH, AP, ILD, and illnesses that may represent one of these conditions in systemic JIA and Still's disease existed in the literature (22)(23)(24)(25)(26)(27), so the number of cases being reported to the Listserv represented an increase. Because IL-1 inhibitors became much more commonly used in systemic JIA in the mid-2000s, there was concern about a possible association between exposure to biologic medications such as IL-1 inhibitors and the development of pulmonary complications in some patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of 19 patients with PAH and various autoimmune diseases was done in northern Taiwan, where PAH has been reported seldom, and revealed that 2 patients had AOSD; in this study, 5 patients died and the RVSP correlated with the levels of serum uric acid ( r = 0.686, P = 0.001) [12]. Another case report described a 29-year-old woman, who 9 years after a diagnosis of AOSD, developed PAH (mean PAP 33 mmHg) responsive to vasodilator infusion, but died 2.5 months later of right heart failure, despite initiation of anakinra [13]. Lastly, a case report from Hyderabad, India, described an 18-year-old female with new onset AOSD who developed severe PAH (mean PAP of 65 mmHg); in the absence of other causes, the authors concluded that the PAH was secondary to the AOSD-related pulmonary microangiopathy [14].…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, the diagnosis of AOSD is usually based on clinical findings after exclusion of other diseases. AOSD usually has a good prognosis, but can be life-threatening, [5] especially when it is complicated with multiple organ failure and DIC caused by SIRS, [610] hemophagocytic syndrome, [1113] thrombotic thrombocytopenic purpura, [5] acute respiratory distress syndrome, [14] diffuse alveolar hemorrhage, [15] pulmonary arterial hypertension, [16] and liver failure. [17] Therefore, these severe complications should not be overlooked when we see patients with AOSD.…”
Section: Discussionmentioning
confidence: 99%